POLA ASUH ORANGTUA KRISTEN SUKU AMBON - Yuel Sumarno; Jannes Eduard Sirait; Alisya Cindy Silooy; Alex Frans Nathanael Nasution (Bethel Press, 2024)
This study aims to analyze the parenting patterns of Ambonese Christian parents, with a particular focus on the interaction between local culture and Christian faith. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and document analysis involving Ambonese Christian parents with school-age children. The findings reveal that Ambonese parenting is shaped by the cultural principle of pela gandong, which emphasizes solidarity, togetherness, and respect, as well as Christian values of love, discipline, and forgiveness. The integration of culture and faith results in a distinctive collective parenting model, where child-rearing is not only the responsibility of the nuclear family but also of the wider community and the church. The study also shows that faith practices—such as family prayer, Bible reading, and children’s involvement in church activities—play a significant role in shaping children’s spiritual identity. However, Ambonese Christian parenting faces modern challenges stemming from globalization, urbanization, and the influence of digital technology, which risk undermining traditional values. The relevance of this parenting model in the modern era lies in parents’ ability to adapt traditional practices to contemporary contexts through open communication, technology guidance, and collaboration with schools and churches. This study contributes to the literature on Christian family education in Indonesia by presenting a contextual parenting model rooted in both culture and faith.